2022
DOI: 10.1093/bib/bbac013
|View full text |Cite
|
Sign up to set email alerts
|

Computational analyses of bacterial strains from shotgun reads

Abstract: Shotgun sequencing is routinely employed to study bacteria in microbial communities. With the vast amount of shotgun sequencing reads generated in a metagenomic project, it is crucial to determine the microbial composition at the strain level. This study investigated 20 computational tools that attempt to infer bacterial strain genomes from shotgun reads. For the first time, we discussed the methodology behind these tools. We also systematically evaluated six novel-strain-targeting tools on the same datasets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…We focused on the sets for the evolutionary and phylogenetic studies, not for the completeness of the assembled genomes in metagenomics. We ended up with the six sets except the one from Alneberg et al We included the Alneberg et al set because it was used in several strain studies [7, 8, 28].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We focused on the sets for the evolutionary and phylogenetic studies, not for the completeness of the assembled genomes in metagenomics. We ended up with the six sets except the one from Alneberg et al We included the Alneberg et al set because it was used in several strain studies [7, 8, 28].…”
Section: Methodsmentioning
confidence: 99%
“…Because of this property of ubiquitous existence and uniqueness in each genome, USCGs are widely used to study the evolution and classification of species [2][3][4]. In the past two decades, with the enormous amount of metagenomic data generated, USCGs are also routinely employed for taxonomic profiling of microbial species and completeness evaluation of metagenome-assembled genomes in shotgun metagenomic studies [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…StrainFinder is a method that assigns strain genotypes and assesses strain frequencies for subpopulations of microbial communities with maximum likelihood estimates based on allele frequencies [53]. Ventolero et al investigated 20 tools that attempt to infer bacterial strain genomes from shotgun read sequences [54]. They systematically evaluated six novel-strain-targeting tools on the same datasets and found that BHap, mixtureS and StrainFinder performed better than other tools.…”
Section: Related Workmentioning
confidence: 99%
“…Reads are short, containing sequencing errors, and mixed with other reads from different species and strains in the sample. Because of the importance of bacterial strains, many studies have explored identifying known and reconstructing novel bacterial strains from shotgun reads or shotgun metagenomics 1820 .…”
Section: Introductionmentioning
confidence: 99%